MODELLING OF HYDRODYNAMICS AROUND AN IMPERMEABLE BREAKWATER: COMPARISON BETWEEN PHYSICAL AND SPH NUMERICAL MODELING - Didier, E.; Neves, D. R. C. B.; Martins, R.; Neves, M. G. (Revista de Engenharia Térmica, 2012)
This work presents the new developments and the validation of a Smoothed Particle Hydrodynamics (SPH) numerical model used in the National Laboratory of Civil Engineering (Laboratório Nacional de Engenharia Civil - LNEC) for studies in coastal engineering processes. Although the model requires a high CPU time, it proved to be very promising in the simulation of complex flows, such as the wave-structure interaction and the wave breaking phenomenon. For the SPH model validation, physical modeling tests were performed in one LNEC’s flume to study the interaction between an impermeable structure and an incident regular wave. The comparison between numerical and experimental results, i.e. free surface elevation, overtopping volume and pressure, shows the good accuracy of the SPH model to reproduce the various phenomena involving on the wave propagation and interaction with the structure, namely the wave breaking, the wave overtopping and the pressure field on the structure.